2020
DOI: 10.3389/fgene.2020.00528
|View full text |Cite
|
Sign up to set email alerts
|

Prime Editing: Genome Editing for Rare Genetic Diseases Without Double-Strand Breaks or Donor DNA

Abstract: An article published in Nature (Anzalone et al., 2019) reports the development of a genome editing experimental approach that mediates all possible base-to-base conversions, "indels, " and combinations in human genome without the need of double-strand breaks (DSBs) or donor DNA (dDNA) templates. Prime editing, the novel method of genome editing, exploits a longer-than-usual single guide RNA (gRNA), known as prime editing gRNA (pegRNA), and a fusion protein consisting of Cas9 H840A nickase fused to an engineere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
10

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 40 publications
0
38
0
10
Order By: Relevance
“…Prime editing, which can be used in biological systems, first searches for the points in the gene that need to be modified, then impose the editing effects, without breaking into double stranded DNA at the target points, through base deletion, insertion, and substitutions. The most notable advantage of this method to CRISPR is that it has less off-target effects and is more precise [ 115 , 116 , 117 ]. This technique is still in its infancy and has not yet been used in pathogenic fungi.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Prime editing, which can be used in biological systems, first searches for the points in the gene that need to be modified, then impose the editing effects, without breaking into double stranded DNA at the target points, through base deletion, insertion, and substitutions. The most notable advantage of this method to CRISPR is that it has less off-target effects and is more precise [ 115 , 116 , 117 ]. This technique is still in its infancy and has not yet been used in pathogenic fungi.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Further shortcomings of the system include the large size of the fusion protein and the potential for random incorporation of cDNAs by the RT [248]. More in-depth reviews on BEs and PEs can be found elsewhere [249][250][251][252][253][254][255].…”
Section: Base and Prime Editorsmentioning
confidence: 99%
“…Despite the advantages of prime-editing technology, the protein structure is currently too large for efficient delivery in vitro or in vivo, and it cannot be used to induce precise modifications in large indel mutations. Therefore, for this approach to be applied more broadly, further research is needed to develop more optimized systems that can overcome current limitations and increase efficiency and specificity [ 39 , 40 ].…”
Section: Programmable Genome Editing Technologies Based On Crispr/mentioning
confidence: 99%